2011
DOI: 10.18097/pbmc20115705490
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mildronate on peripheral neuropathy and some characteristics of glucose and lipid metabolism in rat streptozotocin-induced diabetes mellitus model

Abstract: Крысам со стрептозотоциновой моделью сахарного диабета перорально или внутрибрюшинно вводили милдронат (100 мг/кг ежедневно) в течение 6 недель. Вес животных, развитие невропатических болей, концентрацию глюкозы, триглицеридов и кетоновых тел в крови, процент гликированного гемоглобина, тест толерантности глюкозы определяли в течение всего эксперимента. Милдронат полностью предотвращал развитие диабетической невропатии, с первой недели и до конца эксперимента. В группе животных, получавших милдронат, наблюдали… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
5
0
1
Order By: Relevance
“…Results of this study show that mildronate had a marked and stable positive effect on glucose concentration in blood (Figure 1B and C) and glucose tolerance in animals with streptozotocin diabetes mellitus (Figure 2). These results correlate with literature data 10–12. Data about reduction of HbA1c% in diabetic rats under mildronate treatment (Figure 1D) support the results about positive effect of mildronate on some diabetic complications in humans,4–7 HbA1c being marker of microvascular disease 21…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Results of this study show that mildronate had a marked and stable positive effect on glucose concentration in blood (Figure 1B and C) and glucose tolerance in animals with streptozotocin diabetes mellitus (Figure 2). These results correlate with literature data 10–12. Data about reduction of HbA1c% in diabetic rats under mildronate treatment (Figure 1D) support the results about positive effect of mildronate on some diabetic complications in humans,4–7 HbA1c being marker of microvascular disease 21…”
Section: Discussionsupporting
confidence: 89%
“…In experimental studies the drug manifested an anti‐ketogenic activity in fasting rats 8. It was also shown that mildronate increased the rate of glucose oxidation in rat hearts during hypoxia,9 normalized glucose level in streptozotocin Type 1 diabetes mellitus model in rats and in genetically predisposed to Type 2 diabetes mellitus Goto‐Kakizaki rats 10, 11. Mildronate was also shown to stimulate insulin‐dependent glucose uptake in isolated mice hearts, to increase expression of some proteins involved in glucose metabolism and to decrease blood glucose 12.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In an animal model of diabetes (streptozotocin induced), it was found out that 6 weeks administration of meldonium reduced blood glucose and glycated hemoglobin level, improve glucose tolerance and prevented the development of diabetic associated neuropathy. 24,25 In another experiment with rats; it was observed that meldonium prevents endothelial dysfunctional changes occur with diabetes mellitus. 26 In a clinical study, its role in post infarction period of CHF and diabetes mellitus was well demonstrated, where it tends to normalize the diastolic heart functions and increased the ejection fraction when given along with basic therapy.…”
Section: Pharmacological Action and Therapeutic Usesmentioning
confidence: 99%
“…(2011). Авторами в модели сахарного диабета у крыс в течение 6 недель применения Милдроната показан достоверный эффект по предотвращению нейропатической боли, а также общее снижение средней концентрации глюкозы крови и гликозилированного гемоглобина [15]. Klusa и соавт.…”
unclassified